The Serotonin-Related FEV Gene Variant in the Sudden Infant Death Syndrome is a Common Polymorphism in the African–American Population - Broadbelt, Kevin G. (2009)
An important subset of the sudden infant death syndrome (SIDS) is associated with multiple serotonergic (5-HT) abnormalities in regions of the medulla oblongata. The mouse ortholog of the fifth Ewing variant gene (FEV) is critical for 5-HT neuronal development. A putatively rare intronic variant [IVS2-191_190insA, here referred to as c.128-(191_192)dupA] has been reported as a SIDS-associated mutation in an African-American population. We tested this association in an independent dataset: 137 autopsied cases (78 SIDS, 59 controls) and an additional 296 control DNA samples from Coriell Cell Repositories. In addition to the c.128-(191_192)dupA variant, we observed an associated single base deletion [c.128-(301–306)delG] in a subset of the samples. Neither of the two FEV variants showed significant association with SIDS in either the African-American subgroup or the overall cohort. Although we found a significant association of c.128-(191_192)dupA with SIDS when San Diego Hispanic SIDS cases were compared with San Diego Hispanic controls plus Mexican controls (p=0.04); this became non-significant after multiple testing correction. Among Coriell controls, 33/99 (33%) African-American and 0/197 (0%) of the remaining controls carry the polymorphism (c.128-(191_192)dupA). The polymorphism appears to be a common, likely non-pathogenic, variant in the African-American population.